Exclusive quality: Why exclusive distribution may benefit the TV-viewers - Johan Stennek (Research Institute of Industrial Economics (IFN), 2006)
Sports organizations, Hollywood studios and TV channels grant satellite and cable networks exclusive rights to televise their matches, movies and media contents. Exclusive distributions prevents viewers from watching attractive programs, and reduces the TV-distributors incentives to compete in prices. This paper demonstrates that exclusive distribution may also give providers of contents incentives to invest in higher quality and, as a result, force competitors to reduce their prices. Exclusive distribution may benefit all viewers, including those who are excluded.
Keywords: C78; D43; K21; L42; 330; Exclusive Contracts; Quality; Bargaining; Avertising; Investment; Fernsehen; Fernsehprogramm; Privater Fernsehsender; Gebühr; Dienstleistungsqualität; Wohlfahrtsanalyse